HUBUNGAN POLA ASUH ORANG TUA DENGAN KONSEP DIRI ANAK USIA SEKOLAH (10-12 TAHUN) - Nisha Pramawaty; Elis Hartati (Jurnal Keperawatan Diponegoro, 2012)
Parenting is a process in a family, the interaction between parents and their children. Parenting has been applied since the child was born and adjusted in accordance with the age and stage of development, for example in children aged 10-12 years. The mentioned age is the preadolescent’s period that has various development characteristics that will affect an  individual perspective. Individual knowledge about themselves, the combination of feelings, attitudes, and perceptions are labeled as self-concept. Individual knowledge about themselves, the combination of feelings, attitudes, and perceptions are labeled as self-concept. This study aimed to determine the correlation between parenting style of parents with school-age child’s self concept (10-12 years). The type of research was the non-experimental quantitative with correlation study and data collection using questionnaires. Respondents in this research were children aged 10-12 years and determined by total sampling technique. Total respondents were 149 people. Data were verified by using Chi Square and the results showed that there was correlation between parents’ parenting style with school-age child’s self concept (10-12 years) (x2=6.808; p=0.033). In the authoritatif parenting, more children were found with positive self-concept 73.3%, while the authoritarian and permissive parenting got more children with negative self-concept that was 18.9% and 28.4%. It was suggested that parents should apply authoritatif parenting where children 10-12 year olds with the most positive self-concept are derived from the style, the school and parents should collaborate to improve student achievement accordance with the interests and abilities, community nurses is expected with their role in the community to be able to help locate the problem and provide health education related to parenting style and children’s self-concept